GABAergic signaling is linked to a hypermigratory phenotype in dendritic cells infected by Toxoplasma gondii. - Jonas M Fuks (PLoS Pathogens, 2012)
During acute infection in human and animal hosts, the obligate intracellular protozoan Toxoplasma gondii infects a variety of cell types, including leukocytes. Poised to respond to invading pathogens, dendritic cells (DC) may also be exploited by T. gondii for spread in the infected host. Here, we report that human and mouse myeloid DC possess functional γ-aminobutyric acid (GABA) receptors and the machinery for GABA biosynthesis and secretion. Shortly after T. gondii infection (genotypes I, II and III), DC responded with enhanced GABA secretion in vitro. We demonstrate that GABA activates GABA(A) receptor-mediated currents in T. gondii-infected DC, which exhibit a hypermigratory phenotype. Inhibition of GABA synthesis, transportation or GABA(A) receptor blockade in T. gondii-infected DC resulted in impaired transmigration capacity, motility and chemotactic response to CCL19 in vitro. Moreover, exogenous GABA or supernatant from infected DC restored the migration of infected DC in vitro. In a mouse model of toxoplasmosis, adoptive transfer of infected DC pre-treated with GABAergic inhibitors reduced parasite dissemination and parasite loads in target organs, e.g. the central nervous system. Altogether, we provide evidence that GABAergic signaling modulates the migratory properties of DC and that T. gondii likely makes use of this pathway for dissemination. The findings unveil that GABA, the principal inhibitory neurotransmitter in the brain, has activation functions in the immune system that may be hijacked by intracellular pathogens.